Characterization of Humic Acid and Fulvic Acid Extracted from Soil Samples of Cultivated Areas of North Bengal and Sikkim States, India - Chanda, M.; Jha, S.; Mukhopadhyay, D.; Pandey, M. (Asian Journal of Chemistry, 2020)
Humic acid and fulvic acid extracted from soils of cultivated areas, collected from Majitar, Darjeeling and Pundibari cities were first isolated, purified and then characterized for the physico-chemical properties (oxidizable organic carbon, electrical conductivity, pH, phosphorus, nitrogen, potassium, CEC, etc.). The physico-chemical studies showed that soils were neutral to acidic but are independent of altitude. Organic carbon, available phosphorus, nitrogen were higher with soil of Majitar city. The total acidity, carboxylic group, phenolic -OH group were higher in fulvic acid than in humic acid. Further, both acids were characterized by potentiometric titration, viscometric measurement, surface tension and spectral analysis. The humification index (E4/E6) of fulvic acid was relatively higher than humic acid. The highest molecular weight of humic acid and fulvic acid were recorded 13645.83 and 1465.54, respectively.